Trends on Rural and Urban Entrepreneurship Research - Ni Wayan Anggreni; I Made Artayasa; I Wayan Sukita; I Wayan Sonder; Ida Bagus Nyoman Bala Putra (Universitas Warmadewa, 2024)
This study aims to identify the trends on rural and urban entrepreneurship research. The methodology of this study uses bibliometric analysis. Research data were obtained through the Publish or Perish database with the keywords ‘rural entrepreneurship’ and ‘urban entrepreneurship’ with a publication period from 2014 to 2024. The data that has been collected was then analyzed using VOSviewer software. Based on the results of the study, it can be concluded that entrepreneurship plays an important role in driving economic growth and social development. Rural entrepreneurship mainly focuses on developing rural areas through innovation, managing unique challenges, and strengthening communities, while urban entrepreneurship focuses more on innovation and improving the quality of life in urban environments. Research in both contexts shows diverse trends.